Prospective survey of veterinary practitioners’ primary assessment of equine colic: clinical features, diagnoses, and treatment of 120 cases of large colon impaction - Jennings, Kyra; Curtis, Laila; Burford, John; Freeman, S.L. (BioMed Central, 2014)
Background